2018
DOI: 10.4034/pboci.2018.181.03
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s Knowledge, Attitude and Practice on Prevention of Early Childhood Caries in Al jouf Province, Saudi Arabia

Abstract: Objective: To measure the knowledge, attitude, and preventive practices of parents in regards to their understanding of early childhood caries (ECC) in Al jouf province, Saudi Arabia (KSA). Material and Methods: A cross-sectional oral health survey was conducted among 228 parents, who were selected by stratified cluster sampling. A questionnaire consisting of 10 questions in each domain addressing knowledge, attitude, and preventive practice for ECC was applied. Scoring in the knowledge field included Yes/No/D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
3
0
0
Order By: Relevance
“…A study conducted in India by Nagarajappa et al (2013) showed nearly half of the parents (48.5%) believed that caries occurs after 2 years of age whereas in contrary this study revealed that majority of the participants (90%) stated that caries can occur in under five children. Kumar et al (2018) stated that 51% of the study population accepted that night time bottle feeding affects child's tooth and the similar finding was revealed by the findings of this study (53%). Similarly, in consistency to the finding of only 3% of the participants were able to state the first sign of dental caries as white lines or spots on the tooth surface study by Kumar et al (2018) also revealed only 7% were aware about the first sign of dental caries.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A study conducted in India by Nagarajappa et al (2013) showed nearly half of the parents (48.5%) believed that caries occurs after 2 years of age whereas in contrary this study revealed that majority of the participants (90%) stated that caries can occur in under five children. Kumar et al (2018) stated that 51% of the study population accepted that night time bottle feeding affects child's tooth and the similar finding was revealed by the findings of this study (53%). Similarly, in consistency to the finding of only 3% of the participants were able to state the first sign of dental caries as white lines or spots on the tooth surface study by Kumar et al (2018) also revealed only 7% were aware about the first sign of dental caries.…”
Section: Resultssupporting
confidence: 88%
“…Kumar et al (2018) stated that 51% of the study population accepted that night time bottle feeding affects child's tooth and the similar finding was revealed by the findings of this study (53%). Similarly, in consistency to the finding of only 3% of the participants were able to state the first sign of dental caries as white lines or spots on the tooth surface study by Kumar et al (2018) also revealed only 7% were aware about the first sign of dental caries. This may be due the fact that minor changes are usually ignored as they bring no remarkable changes.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation